2015
DOI: 10.1017/s1368980015000622
|View full text |Cite
|
Sign up to set email alerts
|

Is the future of meat palatable? Perceptions ofin vitromeat as evidenced by online news comments

Abstract: Objective: To understand current public perceptions of in vitro meat (IVM) in light of its potential to be a more environmentally sustainable alternative to conventional meat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(123 citation statements)
references
References 37 publications
9
102
0
Order By: Relevance
“…Such measures may also assist for instance in studies exploring consumer acceptance of lab-grown meat (e.g. Laestadius & Caldwell, 2015;Verbeke, Sans, & Van Loo, 2015;Werbeke et al, 2015). Methodologically, given its psychometric properties, favorable initial evidence concerning its validity, parsimony, and versatility (i.e.…”
Section: Improving Methodologymentioning
confidence: 99%
“…Such measures may also assist for instance in studies exploring consumer acceptance of lab-grown meat (e.g. Laestadius & Caldwell, 2015;Verbeke, Sans, & Van Loo, 2015;Werbeke et al, 2015). Methodologically, given its psychometric properties, favorable initial evidence concerning its validity, parsimony, and versatility (i.e.…”
Section: Improving Methodologymentioning
confidence: 99%
“…In a study funded by New Harvest, an organisation that supports this last technology, it is claimed that in-vitro flesh that is assumed to be able to be cultivated by using cyanobacteria as a growth medium might lower energy use, greenhouse gas emissions, and land and water usage very substantially compared to conventionally produced flesh in Europe, but the authors also point out that its public acceptance may be marred by public concerns over its unnaturalness (Tuomisto and de Mattos 2011), a theme that will be explored in section 2.12. Empirical research, however, has found that this is not the only thing that people are concerned about regarding in-vitro flesh, and that their concerns include issues of safety and taste (Hocquette et al 2015;Laestadius and Caldwell 2015).…”
Section: The Case For a Radical Transformation Of Agriculturementioning
confidence: 99%
“…Even if my concern with safeguarding the integrity of nature is less pronounced with in-vitro flesh than with the genetic engineering of animals, it is not allayed altogether. Research has already found that many invoke the concept of the 'unnatural' when they comment on this former technology (Laestadius and Caldwell 2015). I think that people are right to invoke this concept in this context: cultured flesh is more unnatural than conventional methods to produce flesh as stem cells do not grow into flesh outside living bodies without human intervention.…”
Section: Human Health and In-vitro Fleshmentioning
confidence: 99%
“…Next, Laestadius and Caldwell (2015) assessed U.S. consumer comments on online news stories about cultured meat. They found that the majority of comments contained negative statements about cultured meat, and many of the commentators described the product as unnatural and unappealing (Laestadius & Caldwell, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Next, Laestadius and Caldwell (2015) assessed U.S. consumer comments on online news stories about cultured meat. They found that the majority of comments contained negative statements about cultured meat, and many of the commentators described the product as unnatural and unappealing (Laestadius & Caldwell, 2015). More recently, Wilks and Phillips (2017) surveyed 673 U.S. adults, over half of whom indicated that they were willing to try cultured meat, but only one-third of whom reported willingness to eat cultured meat regularly.…”
Section: Introductionmentioning
confidence: 99%